CALCULATION OF THE RELATIVE AREA OF REGULAR MICRORELIEFS - DZYURA, VOLODYMYR; SEMEHEN, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
An analysis of the methods of forming regular micro reliefs on the flat surfaces of machine parts and methods of determining the operational properties of surfaces with formed regular micro reliefs with different geometric parameters was carried out. According to the analysis results, it was established that the operational properties of surfaces with formed planar regular micro reliefs are best evaluated by the parameter - the relative area of ​​the micro relief, which determines the operational properties of such surfaces. The optimal value of this parameter depends on specific operating conditions. Also, the operational properties are affected by the type of micro relief, which is determined by the interaxial distance of the grooves of the regular micro relief. Schemes of formation of partially regular micro reliefs with non-intersecting grooves (I type), intersecting (III type) and fully regular micro reliefs (IV type) are considered. Analytical dependences were obtained for determining the relative area of ​​regular and partially regular micro reliefs with different interaxial distances of the grooves and taking into account the area of ​​their overlap. Graphical dependences were constructed to determine the relative area of ​​regular micro reliefs depending on the geometrical parameters of the micro relief, tool feed speed, and the number of double moves, as the most influential parameters on the relative area of ​​the micro relief. It was established that the change in the relative area of ​​the micro relief is influenced to a greater extent by the change in the technological modes of the formation of the micro relief - feed speed and the number of double strokes, and to a lesser extent by the geometric parameters of the micro relief - amplitude and step.
Keywords: regular micro relief; relative area; grooves; modes of formation; parameters; overlapping area; surface